IDIOMS IN THE SONG LYRICS OF ARIANA GRANDE’S “MY EVERYTHING” ALBUM - Ndruru, Murniwati (Research on English Language Education, 2024)
This research was carried out to investigate the idiom in the song lyrics of Ariana Grande’s “My Everything” album. The objectives of this research were to find out the types of idioms and to describe the meaning of idioms found in the song lyrics of Ariana Grande’s “My Everything” album. This research was designed to qualitative research. The researcher collected and classified the data in seven types of idioms suggested by O’Dell & McCarthy and after obtaining the data, the researcher analyzed the data by applying data reduction, data display, drawing conclusion and verification. The result of this research showed that there were various idioms found in the song lyrics of Ariana Grande’s “My Everything” album such as similes, binomials, proverbs, euphemisms, cliché, fixed statements and other language. Each of idioms has their own meaning and they were interpreted based on their context in using them. Idioms obviously most found in the song and it really helps people to enrich their vocabularies and expand their understanding about all expressions in English. The researcher suggested to the students to read this thesis to be able know the context of idioms and also interpret the meaning of idioms. Morever, the researcher also suggested to the other researcher to complete the further research better and provide more explanation and also they can use this research as their reference.